Modelling the Mediating Effect of Health Care Healing Environment on Core Health Care Delivery and Patient Satisfaction in Ghana - Amankwah, Oti (Environ Health Insights, 2019)
OBJECTIVE: The multifaceted nature of health care delivery has led to the need to incorporate strategies that will help to enhance performance and maintain the quality of the health care environment. However, even though dedicated health care staffs contribute to patients’ satisfaction of health care delivery, the health care environment must ensure the safety and well-being of patients. Like most developing countries, many public hospitals in Ghana are faced with challenges in the area of health care healing environment. Therefore, this article investigates the mediating effect of health care healing environment between health care core business and patients’ satisfaction. METHOD: This is a cross-sectional study involving adult patients of Komfo Anokye Teaching Hospital, Tamale Teaching Hospital, and Cape Coast Teaching Hospital in Ghana. A questionnaire survey based on the ‘A Staff and Patient Environment Calibration Toolkit (ASPECT)’ dimensions and health care core service dimensions was used to collect data from 622 patients. SmartPLS was used to analyse the data collected. RESULTS: The findings of the study show that the quality of health care healing environment mediates the relationship between patients’ satisfaction and all of the constructs under the core health care delivery. CONCLUSION: Stakeholders of the Ghanaian health care sector should take initiatives to constantly improve the quality of health care healing environment as it has an influence on patient satisfaction of the overall core health care delivery.